2019
DOI: 10.1039/c9sc03431e
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures of bent lanthanide(III) complexes with two N-donor ligands

Abstract: Low coordinate metal complexes can exhibit superlative physicochemical properties, but this chemistry is challenging for the lanthanides (Ln) due to their tendency to maximize electrostatic contacts in predominantly ionic bonding regimes. Although a handful of Ln 2+ complexes with only two monodentate ligands have been isolated, examples in the most common +3 oxidation state have remained elusive due to the greater electrostatic forces of Ln 3+ ions. Here, we report bent Ln 3+ complexes with two bis(silyl)amid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…Thereby, the Ce–P distances are slightly longer than in previously reported Ce­(III) phosphine complexes, , but are in the same range as the recently reported complexes by Schelter et al A similar elongation is also observed for the Ln1–N1 bonds from 2.373(3) Å in 1-La to 2.436(3) Å in 8-La and from 2.333(3) Å in 1-Ce to 2.408(4) Å in 8-Ce . The distances of the lanthanide atom to the silylamide nitrogen atoms in 8-La and 8-Ce are in the range of previously reported Ln­(HMDS) x complexes. , For further crystallographic information see the Supporting Information, Tables S1–S5.…”
Section: Resultsmentioning
confidence: 66%
“…Thereby, the Ce–P distances are slightly longer than in previously reported Ce­(III) phosphine complexes, , but are in the same range as the recently reported complexes by Schelter et al A similar elongation is also observed for the Ln1–N1 bonds from 2.373(3) Å in 1-La to 2.436(3) Å in 8-La and from 2.333(3) Å in 1-Ce to 2.408(4) Å in 8-Ce . The distances of the lanthanide atom to the silylamide nitrogen atoms in 8-La and 8-Ce are in the range of previously reported Ln­(HMDS) x complexes. , For further crystallographic information see the Supporting Information, Tables S1–S5.…”
Section: Resultsmentioning
confidence: 66%
“…In recent years, lanthanide ion (Ln 3+ )-based PBAs have attracted a great deal of attention due to their unique properties, allowing them to generate new physicochemical effects that are not available for d-block paramagnetic metal complexes. The presence of shielded f-electron ions enables them to acquire properties such as luminescence and high magnetic anisotropy associated with slow magnetic relaxation processes. Therefore, these assemblies are predisposed to demonstrate strong optical emission and single-molecule magnet (SMM) behaviors. …”
Section: Introductionmentioning
confidence: 99%
“…Room temperature solution phase magnetic moments determined for 1-E and 2-E 2 using the Evans method are consistent with other Sm­(III)-N †† species (Table ). , The solution moments for 1-E are higher than the room temperature χ M T products that range 0.14–0.19 cm 3 K mol –1 from magnetometric measurements on powder samples, though both are noticeably larger than the free-ion value for a 6 H 5/2 multiplet at 0.09 cm 3 K mol –1 . This is characteristic of Sm­(III), where the observed moment is dominated by temperature independent paramagnetism from second-order mixing with low-lying excited states. , On cooling, χ M T steadily decreases to 0.03 cm 3 K mol –1 at 2 K (Figures S45, S47, and S49).…”
Section: Resultsmentioning
confidence: 90%
“…There are numerous examples of analogous reactions across the f block, ,,, and these polar M–ER groups (M = Ln or An) are amenable to further derivatization . We have previously shown that although the ligand framework in [Sm­(N †† ) 2 ] is sterically demanding, the two bis­(triisopropylsilyl)­amide ligands are flexible enough to bend toward each other to accommodate further moieties at the Sm center, thus we envisaged that this redox strategy would afford a series of structurally similar complexes. ,, Gratifyingly, the separate reactions of [Sm­(N †† ) 2 ] with half an equivalent of E 2 Ph 2 in toluene gave the heteroleptic Sm­(III) complexes [Sm­(N †† ) 2 (EPh)] (E = S, 1-S ; Se, 1-Se ; Te, 1-Te ; Scheme ) in moderate to excellent yields (52–93%). Previously, Ln–EPh moieties have been investigated toward reductive elimination of E 2 Ph 2 in order to access Ln redox chemistry while avoiding the challenging synthesis of divalent precursors …”
Section: Resultsmentioning
confidence: 99%